Establishing Single Data for PTKIN: National Data Dictionary Mandate and Quality Audit Towards Accountability - Yayuk Sri Rahayu (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper analyzes the weaknesses of data-based decision-making governance policies at State Islamic Religious Colleges (PTKIN). This crucial issue is raised in this policy article, rooted in the disintegration of the service system that causes the use of different data standards across work units, resulting in acute, inconsistent data fragmentation, and hindering accurate and rapid strategic decision-making. The methodology used is descriptive qualitative analysis, utilizing problem prioritization using the Urgency, Seriousness, Growth (USG) method and evaluation of alternative regulatory policies using William N. Dunn's scoring theory. This writing is also supported by an in-depth review of existing Ministry of Religious Affairs regulations (such as PMA No. 1 of 2023 concerning One Data of the Ministry of Religious Affairs) and data management theories such as data governance and bounded rationality. The results and discussion indicate that the main root of the problem lies in the failure of harmonization and standardization of data across services, which is a manifestation of the weakness of central governance policies. Based on Dunn's analysis, the most effective policy is the establishment of the KMA on the Establishment of a National Data Dictionary for PTKIN as a fundamental prerequisite, directly addressing this problem by establishing a single, legally binding data language standard for all PTKIN. This is the most crucial and fundamental step because it resolves the problem of data inconsistency at the source to enforce compliance, in order to achieve a Single Source of Truth and effective data-driven management.